MENCIPTAKAN PENGALAMAN KONSUMENDENGAN EXPERIENTIAL MARKETING - Yoyon Safrianto (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2017)
AbstractExperiential marketing gives customers an opportunity to engage and interact with brands,products, and services in sensory ways that provide the icing on the cake of providing information. Personalexperiences help people connect to a brand and make intelligent and informed purchasing decisions. Theterm “experiential marketing” refers to actual costomers esperiences with the brand/product/services thatdrive sales and increase brand image and awareness through sense, feel, think, act, and relate to Companyand Brands. It’s difference between telling people about features of product or service and letting themexperience the benefits for themselves. When done right, it’s the most powerfull tool out there to win brandloyalty.Keywords: sense, feel, think, act, and relate